Study of Mangrove Ecosystem Potential in Management as Ecoturism Area in Teling Village, Tombariri District, Minahasa Regency, North Sulawesi Province - Rolley M.E.F. Pesik; Adnan S. Wantasen; Febri S.I. Menajang; Anthonius P. Rumengan; Noldy G.F. Mamangkey; Joice R.T.S.L. Rimper; Deiske A. Sumilat; Joshian N.W. Schaduw (Sam Ratulangi University, 2025)
The purpose of this study is to analyze the potential conditions of the mangrove ecosystem, land suitability, conditions and perceptions of the Teling village community to be developed as an ecotourism area. The survey of the potential of the mangrove ecosystem used the transect-quadrant method, while the potential for socio-economic conditions, infrastructure and perceptions of the Teling village community was carried out using the interview method. There are 6 (six) types of mangroves found in Teling Village, namely Avicennia officinalis, Bruguiera gymnorrhiza, Rhizophora mucronata, Sonneratia alba and Sonneratia caseolaris. The mangrove species with the highest average density value is R. mucronata at 33.33 individuals/300m², the highest average frequency value is found in the B. gymnorrhiza and R. stylosa species, which is 0.89, the highest average cover value is found in the S. alba species, which is 1.0265 m2/300 m2, the highest average Importance Value Index (INP) is found in the Rhizophora mucronata species, which is 111.0 with the